2013
DOI: 10.5830/cvja-2013-042
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of effusive constrictive pericarditis

Abstract: BackgroundThe surgical approach for effusive constrictive pericarditis (ECP) has not been extensively studied. We present our institution’s early and long-term results of pericardiectomy in our cohort of patients with ECP.MethodsDiagnosis was made primarily by echocardiography. Right heart catheterisation was performed in eight patients. Pre-operatively, 10 patients had undergone at least one previous attempt at therapeutic pericardiocentesis. Pericardiectomy was performed where appropriate (thickened or infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…4,5,14 These observations are in distinct contrast to other regions, such as Asia, Africa, and India, in which tuberculosis is recognized as a major cause ranging from 61% to 93%. 4,[9][10][11][12][13] The numerous causative factors predisposing to the development of pericarditis poses a challenge in evaluating its natural history and outcomes after surgical treatment. Because of this, we deliberately selected a homogeneous cohort of patients; choosing patients who were undergoing isolated pericardiectomy in an effort to better define the natural postoperative history, but avoiding the potentially confounding influence of other procedures.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,14 These observations are in distinct contrast to other regions, such as Asia, Africa, and India, in which tuberculosis is recognized as a major cause ranging from 61% to 93%. 4,[9][10][11][12][13] The numerous causative factors predisposing to the development of pericarditis poses a challenge in evaluating its natural history and outcomes after surgical treatment. Because of this, we deliberately selected a homogeneous cohort of patients; choosing patients who were undergoing isolated pericardiectomy in an effort to better define the natural postoperative history, but avoiding the potentially confounding influence of other procedures.…”
Section: Commentmentioning
confidence: 99%
“…3,4 Despite having vastly different pathophysiology-constriction with loss of pericardial compliance and resultant diastolic heart failure and effusive/chronic relapsing pericarditis with recurrent chest pain and pericardial effusion-both benefit from removal of the pericardium to achieve symptomatic relief and improvement in functional status. [3][4][5][6][7][8][9] Although, there are many reports validating the benefit of pericardiectomy, there remains a poor understanding of which patients derive the most benefit from surgery, 4,[10][11][12][13] what comorbid conditions contribute most to postoperative morbidity and mortality, the superiority of a particular surgical approach, or, most importantly, the long-term outcomes after intervention.…”
mentioning
confidence: 99%
“…Studies in humans with contrictive pericarditis secondary to tuberculosis have shown that right atrial pressures improve following partial pericardiectomy performed through a lateral thoracotomy, albeit to a lesser extent than if total pericardiectomy is performed via sternotomy 37 . A decrease in central venous and right atrial pressures has been reported after total or partial pericardiectomy in humans with constrictive pericarditis but we are unaware of similar postoperative pressure studies in dogs with constrictive pericarditis 37,38 . Changes in central venous pressures were not observed after near‐total pericardiectomy via a right lateral approach in one published study in dogs with chylothorax where parietal pericardium was removed from the base of the pulmonary vessels on the right to just ventral to the phrenic nerve on the left 4 .…”
Section: Discussionmentioning
confidence: 84%
“…37 A decrease in central venous and right atrial pressures has been reported after total or partial pericardiectomy in humans with constrictive pericarditis but we are unaware of similar postoperative pressure studies in dogs with constrictive pericarditis. 37,38 Changes in central venous pressures were not observed after near-total pericardiectomy via a right lateral approach in one published study in dogs with chylothorax where parietal pericardium was removed from the base of the pulmonary vessels on the right to just ventral to the phrenic nerve on the left. 4 Additional studies in dogs have described successful resolution of chylothorax when TD ligation and subphrenic pericardiectomy was performed via right lateral thoracotomy, where pericardial access would be expected to be similar to the left-sided approach described in this study.…”
Section: Discussionmentioning
confidence: 99%